Hemispheric asymmetry and atypical lobar progression of Alzheimer‐type tauopathy. (20th December 2022) - Tremblay, Cécilia; Serrano, Geidy E; Intorcia, Anthony J; Sue, Lucia I; Nelson, Courtney M; Walker, Jessica; Arce, Richard; Fleisher, Adam S; Pontecorvo, Michael J.; Atri, Alireza; Montine, Thomas J.; Chen, Kewei; et al.
Abstract: Background: Neurofibrillary tau pathology spread in Alzheimer's disease (AD) mostly shows a stereotypical pattern of topographical progression. Atypical patterns have also been described and associated with interhemispheric asymmetry. As histopathological studies that used bilateral sampling are limited, this study aimed to assess interhemispheric tau pathology differences and the presence of topographically atypical cortical spreading patterns. Method: Immunohistochemical staining for detection of tau pathology was performed in 23 regions of interest of 57 autopsy cases and compared between cortical regions and hemispheres. Result: Frequent mild (82% of cases) and occasional moderate (32%) interhemispheric density discrepancies were observed while marked discrepancies were uncommon (7%) and restricted to occipital regions. Left and right hemispheric tau pathology dominance was observed with similar frequencies, except in Braak stage VI that favored a left dominance. Interhemispheric Braak stage differences were observed in 16% of cases and was more frequent in advanced (IV‐VI) than early stages (I‐III). One atypical lobar topographical pattern, where occipital tau pathology density exceeded frontal lobe scores, was identified in 4 cases, favoring a left dominant asymmetry. Conclusion: We speculate that asymmetry and atypical topographical progression patterns may be associated with described atypical AD clinical presentations and progression characteristics, which should be tested by comprehensive clinicopathological correlations.